(untitled) (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
The study focuses on the practical application of the European Union Carbon Certification Framework (CRCF) in agriculture. The aim of the work is to develop a framework that helps farmers and policymakers evaluate different carbon-related farming practices, such as agroforestry and soil improvement. The study uses multi-criteria analysis to evaluate practices not only according to their climate impact, but also according to their economic viability, implementation complexity and environmental co-benefits. The results offer a structured decision-making tool that facilitates the implementation of CRCF requirements on real farms, helping to identify the most suitable solutions for sustainable agriculture.